Bonding wire for semiconductor device
By forming a coating layer with a specific structure on the Cu or Cu alloy core material, the problem of oxidation and corrosion of the Cu bonding wire under a high temperature environment is solved, and the shape stability and joint reliability of the second bonding part are improved.
Patent Information
- Application Number
- CN202380049084.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-21
- Publication Date
- 2025-02-11
AI Technical Summary
The existing Cu bonding wire is prone to surface oxidation under high temperature environments, resulting in electrochemical corrosion, affecting the bonding reliability of the second joint. At the same time, when the second bonding is stable on the external electrode with a narrow spacing, the fish tail shape is Inadequate symmetry and dimensional stability.
A core material composed of Cu or Cu alloy is used, and a coating layer containing conductive metal other than Cu is formed on its surface. The average dimension of the linear circumference of the grain is analyzed by the EBSD method, and the concentration in the depth direction is measured by the AES method. Distribution ensures the specific concentration distribution of elements such as Pd, Pt, Au, Ni, Ag, etc. in the coating layer.
The shape stability and joint reliability of the second joint are improved, especially in severe high temperature environments, local corrosion of Cu is avoided, and the long-term stability and reliability of the joint wire are ensured.
Smart Images

Figure BDA0005202907950000351 
Figure BDA0005202907950000361 
Figure HDA0005202907970000011
Abstract
Description
Technical Field
[0001] The present invention relates to a bonding wire for a semiconductor device and also to a semiconductor device including the bonding wire. Background Art
[0002] In a semiconductor device, the electrodes formed on the semiconductor chip are connected to the electrodes on the lead frame or substrate by bonding wires. The bonding wire connection process is completed by using a cylindrical bonding tool (cutter) through which the bonding wire is passed for connection, and the first bonding is performed with the electrode on the semiconductor chip, and then after forming a wire arc, the wire portion is bonded to an external electrode such as an electrode on the lead frame or substrate for the second bonding. The first bonding is to heat and melt the front end of the wire portion (hereinafter also referred to as the "tail") extending from the chopper using arc heat input, and form a free air ball (FAB: Free Air Ball; hereinafter also referred to as "ball") by surface tension, and then the ball portion is crimped and bonded to the electrode on the semiconductor chip (hereinafter also referred to as "ball bonding"). In addition, the second bonding does not form a ball, but is crimped and bonded to the external electrode by applying ultrasonic waves and loads to the wire portion from the chopper (hereinafter also referred to as "wedge bonding"). Then, after the connection process, the bonding portion is sealed with a sealing resin to obtain a semiconductor device.
[0003] Until now, gold (Au) has been the mainstream material for bonding wires, but substitution with copper (Cu) is being promoted, mainly for LSI applications (for example, Patent Documents 1 to 3). In addition, against the background of the popularity of electric vehicles and hybrid vehicles in recent years, in the use of vehicle-mounted devices, and in the use of power devices (power semiconductor devices) in high-power devices such as air conditioners and solar power generation systems, due to high thermal conductivity and high fusing current, it is expected to be replaced by Cu, which has high efficiency and reliability.
[0004] Cu has the disadvantage of being easily oxidized compared to Au, and as a method of preventing the surface oxidation of Cu bonding wire, a structure in which the surface of the Cu core material is coated with a metal such as Pd has been proposed (Patent Document 4). In addition, a Pd-coated Cu bonding wire has been proposed in which the surface of the Cu core material is coated with Pd, and Pd and Pt are further added to the Cu core material to improve the bonding reliability of the first bonding portion (Patent Document 5).
[0005] Prior Art Literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 61-48543
[0008] Patent Document 2: Japanese Patent Application No. 2018-503743
[0009] Patent Document 3: International Publication No. 2017 / 221770
[0010] Patent Document 4: Japanese Patent Application Publication No. 2005-167020
[0011] Patent Document 5: International Publication No. 2017 / 013796 Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] As described above, in the second bonding, the wire is crimped and bonded to the external electrode by applying ultrasonic waves and loads to the wire portion from the splitting knife. In more detail, the second bonding is composed of a stitch bonding in which the wire is bonded to the external electrode by pressing the wire with the front end of the splitting knife, and a tail bonding for the purpose of temporary bonding for forming a tail as a preparation for forming the FAB in the next process. The temporary wire bonding portion of the tail bonding is formed corresponding to the edge of the wire supply opening at the front end of the splitting knife, and is peeled off together with the tail when a certain length of the tail is ensured. In this way, by peeling off the temporary wire bonding portion of the tail bonding from the wire crimping portion deformed by the stitch bonding, the second bonding portion formed on the external electrode has a fishtail shape (fish tail fin shape) (refer to Figure 1 ; The second bonding portion is indicated by reference numeral 10). In this regard, as the fine pitch of external electrodes is developed along with the miniaturization and multi-pinning of semiconductor devices, when the second bonding is stably performed on the small-area external electrodes arranged at a narrow pitch, and when good continuous bonding is achieved, represented by the stabilization of the size of the FAB formed in the next process, it is required to further improve the shape stability of the second bonding portion such as the symmetry of the above-mentioned fishtail shape and dimensional stability with respect to the bonding wire used.
[0014] In addition, in-vehicle devices or power devices tend to be exposed to higher temperatures during operation than general electronic devices, and the bonding wires used are required to exhibit good bonding reliability in severe high-temperature environments. In this regard, it has been confirmed that in the existing Cu bonding wires with a Pd coating layer, the Pd coating layer is partially peeled off during the wire connection process, and the Cu of the core material is exposed. The contact area between the coated Pd portion and the exposed Cu portion is exposed to an environment containing oxygen or water vapor generated from the sealing resin, and sulfide-based exhaust gas in a high-temperature environment, resulting in local corrosion of Cu, that is, electrochemical corrosion, and sometimes the bonding reliability of the second bonding portion cannot be fully obtained.
[0015] First, the present invention provides a new Cu bonding wire that provides good shape stability of the second bonding portion.
[0016] Second, the present invention provides a novel Cu bonding wire that provides good shape stability of the second bonding portion and good bonding reliability of the second bonding portion even in a severe high temperature environment.
[0017] Technical means for solving technical problems
[0018] The present inventors have conducted intensive studies on the above-mentioned problems and have found that the above-mentioned problems can be solved by having the following configuration, thereby completing the present invention.
[0019] That is, the present invention includes the following contents.
[0020] [1] A bonding wire for a semiconductor device, comprising a core material made of Cu or a Cu alloy and a coating layer formed on a surface of the core material and containing a conductive metal other than Cu,
[0021] The average size of the grains in the circumferential direction of the wire obtained by analyzing the surface of the wire by the electron backscatter diffraction (EBSD) method is 35 nm or more and 140 nm or less;
[0022] In the concentration distribution in the depth direction of the line measured by Auger electron spectroscopy (AES), the region from the surface to a depth of 10 nm (hereinafter referred to as “region d 0-10 ”.) contains three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, and satisfies the following concentration conditions (i) and (ii):
[0023] (i) Regarding area d 0-10 At least three of the three or more elements contained in the region d 0-10 The average concentration of each element in the
[0024] (ii) Regarding area d 0-10 All of the three or more elements contained in the region d 0-10 The average concentration of each element in the carbon nanotubes is less than 80 atomic %.
[0025] [2] The bonding wire as described in [1],
[0026] The thickness of the coating layer is not less than 40 nm and not more than 200 nm.
[0027] [3] The bonding wire according to [1] or [2],
[0028] In the results of measuring the crystal orientation of the surface of the wire by the EBSD method, the crystal orientation in the wire length direction with an angle difference of 15 degrees or less relative to the wire length direction is <111> The ratio of the crystal orientation is 30% or more and 95% or less.
[0029] [4] The bonding wire according to any one of [1] to [3],
[0030] The concentration distribution in the depth direction of the wire was obtained by digging down from the surface of the wire by Ar sputtering and measuring by AES under the following conditions:
[0031] <Conditions> The line is positioned so that the center of the line width is the center of the measurement surface width, the measurement surface width is 5% to 15% of the line diameter, and the measurement surface length is 5 times the measurement surface width.
[0032] [5] The bonding wire according to any one of [1] to [4],
[0033] The wire contains one or more elements selected from the group consisting of B, P, In and Mg (hereinafter referred to as "first additional elements"), and the total concentration of the first additional elements relative to the entire wire is 1 mass ppm to 100 mass ppm.
[0034] [6] The bonding wire according to any one of [1] to [5],
[0035] It contains one or more elements selected from the group consisting of Se, Te, As and Sb (hereinafter referred to as "second additional elements"), and the total concentration of the second additional elements relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.
[0036] [7] The bonding wire according to any one of [1] to [6],
[0037] It contains one or more elements selected from the group consisting of Ga, Ge, and Ag (hereinafter referred to as "third additional elements"), and the total concentration of the third additional elements relative to the entire wire is 0.011 mass % to 1.5 mass %.
[0038] [8] A semiconductor device,
[0039] Includes the bonding wire according to any one of claims [1] to [7].
[0040] Effects of the Invention
[0041] According to the present invention, it is possible to provide a new Cu bonding wire that provides good shape stability of the second bonding portion.
[0042] According to the present invention, it is possible to provide a new Cu bonding wire that provides good shape stability of the second bonding portion and good bonding reliability of the second bonding portion even in a severe high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a schematic diagram for explaining the second joining portion.
[0044] Figure 2 This is a schematic diagram for explaining the position and size of a measurement surface when measuring the width of a grain on a line surface by the EBSD method or performing a composition analysis by AES.
[0045] Figure 3 This is a schematic diagram of the concentration distribution in the depth direction of the line obtained by measuring the line according to one embodiment of the present invention by AES.
[0046] Figure 4 This is a schematic diagram of the concentration distribution in the depth direction of the line obtained by measuring the line according to one embodiment of the present invention by AES.
[0047] Figure 5 This is a schematic diagram of the concentration distribution in the depth direction of the line obtained by measuring the line according to one embodiment of the present invention by AES. DETAILED DESCRIPTION
[0048] Hereinafter, the present invention will be described in detail according to preferred embodiments. In the description, reference is sometimes made to the accompanying drawings, but the accompanying drawings only schematically illustrate the shapes, sizes and configurations of the constituent elements to the extent that the invention can be understood. The present invention is not limited to the following embodiments and illustrative objects, and can be implemented with any changes without departing from the scope of protection of the present invention and its equivalent scope.
[0049] [Bonding wire for semiconductor devices]
[0050] The bonding wire for semiconductor device of the present invention (hereinafter also referred to as "wire of the present invention" or "wire") is characterized by comprising a core material composed of Cu or a Cu alloy, and
[0051] A coating layer containing a conductive metal other than Cu formed on the surface of the core material;
[0052] The average size of the grains in the circumferential direction of the wire obtained by analyzing the surface of the wire by the electron backscatter diffraction (EBSD) method is 35 nm or more and 140 nm or less;
[0053] In the concentration distribution in the depth direction of the line measured by Auger electron spectroscopy (AES), the region from the surface to a depth of 10 nm (hereinafter referred to as “region d 0-10 ”.) contains three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, and satisfies the following concentration conditions (i) and (ii):
[0054] (i) Regarding area d0-10 At least three of the three or more elements contained in the region d 0-10 The average concentration of each element in the
[0055] (ii) Regarding area d 0-10 All of the three or more elements contained in the region d 0-10 The average concentration of each element in the carbon nanotubes is less than 80 atomic %.
[0056] As described above, the second bonding portion formed on the external electrode has a fishtail shape (a tail fin shape of a fish). Figure 1 FIG. 2 is a schematic diagram showing a state where a second bonding portion formed on an external electrode is viewed from directly above in a direction perpendicular to the main surface of the external electrode. Figure 1 In the example, a second bonding portion 10 in a fishtail shape is formed at the right end of line 1. When the second bonding is stably performed on a small-area external electrode arranged at a narrow pitch, and when good continuous bonding is achieved, represented by stabilization of the size of the FAB formed in the next process, the fishtail shape of the second bonding portion is preferably well symmetrical. Figure 1 In the embodiment, the axis of the wire is represented by a single dotted line X extending in the left-right direction, and the fishtail shape of the second joint portion is preferably well symmetrical with respect to the axis of the wire. From the same viewpoint as above, the fishtail shape of the second joint portion is preferably well dimensionally stable. Specifically, when multiple second joints are performed continuously, the deformation length ( Figure 1 The dimension of the second joint portion 10 in the left-right direction), the deformation width in the direction perpendicular to the axis of the wire ( Figure 1 A fishtail shape with small deviation is realized in the dimension 10w in the vertical direction of the second bonding portion 10. When the second bonding is stably performed on a small-area external electrode arranged at a narrow pitch, it is particularly preferred to realize a fishtail shape with small deviation in the deformation width in the direction perpendicular to the axis of the wire.
[0057] The inventors have conducted in-depth research on the improvement of the shape stability of the second joint, such as the symmetry and dimensional stability of such a fishtail shape, and have found that a bonding wire comprising a core material composed of Cu or a Cu alloy and a coating layer containing a conductive metal other than Cu formed on the surface of the core material can provide good shape stability of the second joint, wherein the average size of the grains in the circumferential direction of the wire obtained by analyzing the surface of the wire by the electron backscatter diffraction (EBSD) method is 35 nm or more and 140 nm or less, and in the concentration distribution in the depth direction of the wire measured by AES, the region from the surface to a depth of 10 nm contains three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, and satisfies the above-mentioned concentration conditions (i) and (ii). Furthermore, the inventors have found that the bonding wire having the coating layer having the above-mentioned specific structure can provide good bonding reliability of the second joint even when exposed to a severe high temperature environment exceeding 175°C. As described above, the present invention significantly contributes to miniaturization and pin multiplication of semiconductor devices, and further significantly contributes to practical application and promotion of Cu bonding wires in automotive devices and power devices.
[0058] <Core Material Made of Cu or Cu Alloy>
[0059] The wire of the present invention includes a core material composed of Cu or a Cu alloy (hereinafter, also simply referred to as a "Cu core material").
[0060] The Cu core material is not particularly limited as long as it is composed of Cu or a Cu alloy, and a known Cu core material constituting a conventional Pd-coated Cu wire known as a bonding wire for a semiconductor device can be used.
[0061] In the present invention, the concentration of Cu in the Cu core material, for example, in the center (axial portion) of the Cu core material can be 97 atomic % or more, 97.5 atomic % or more, 98 atomic % or more, 98.5 atomic % or more, 99 atomic % or more, 99.5 atomic % or more, 99.8 atomic % or more, 99.9 atomic % or more, or 99.99 atomic % or more.
[0062] The Cu core material may contain, for example, one or more dopants selected from the first additional element, the second additional element, and the third additional element described below. The preferred contents of these dopants are described below.
[0063] In a preferred embodiment, the Cu core material is composed of Cu and inevitable impurities. In another preferred embodiment, the Cu core material is composed of Cu, one or more elements selected from the first additional element, the second additional element, and the third additional element described later, and inevitable impurities. In addition, the term "inevitable impurities" for the Cu core material also includes elements constituting the coating layer described later.
[0064] <Coating layer>
[0065] The wire of the present invention includes a coating layer (hereinafter also simply referred to as a "coating layer") formed on the surface of a Cu core material and containing a conductive metal other than Cu.
[0066] From the viewpoint of achieving good shape stability of the second joint and further from the viewpoint of achieving good bonding reliability of the second joint even in a severe high temperature environment, it is important that the coating layer of the wire of the present invention satisfies the following two conditions (1) and (2).
[0067] (1) The average size of the crystal grains in the circumferential direction of the wire, which is obtained by analyzing the surface of the wire by the EBSD method, is 35 nm or more and 140 nm or less.
[0068] (2) In the concentration distribution in the depth direction of the line measured by AES, the region from the surface to a depth of 10 nm (“region d 0-10 ”) contains three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, and satisfies the following concentration conditions (i) and (ii):
[0069] (i) Regarding area d 0-10 At least three of the three or more elements contained in the region d 0-10 The average concentration of each element in the
[0070] (ii) Regarding area d 0-10 All of the three or more elements contained in the region d 0-10 The average concentration of each element in the carbon nanotubes is less than 80 atomic %.
[0071] - Condition (1) -
[0072] The condition (1) relates to the average size of the crystal grains in the line circumferential direction ("width of the crystal grains") obtained by analyzing the surface of the line by the EBSD method.
[0073] In combination with condition (2), by including a coating layer that satisfies condition (1), the wire of the present invention can bring about good shape stability of the second joint. Furthermore, even in a harsh high temperature environment, it can bring about good joining reliability of the second joint. The grains on the surface of the wire form a structure that is elongated in the length direction of the wire. According to the research of the inventors, it was found that reducing the average size of the grains in the circumferential direction of the wire, that is, the width of the grains, to a certain range is effective in improving the shape stability and joining reliability of the second joint. In comparison, it was confirmed that it is difficult to improve the shape stability and joining reliability of the second joint by controlling the average length of the grains in the length direction of the wire or controlling the average grain size of the grains converted to an equivalent circle.
[0074] Regarding condition (1), from the perspective of achieving good shape stability of the second joint, especially the symmetry of the fishtail shape, the width of the grain obtained by analyzing the surface of the wire of the present invention by the EBSD method is 140nm or less, preferably 135nm or less, 130nm or less, or 125nm or less, more preferably 120nm or less, or 110nm or less, and further preferably 100nm or less, 95nm or less, or 90nm or less. In particular, if the width of the grain is 100nm or less, it is easy to achieve better symmetry of the fishtail shape and is preferred. In addition, the inventors have confirmed that if the width of the grain is within the above range, it is easy to achieve excellent bonding reliability of the second joint even in a harsh high temperature environment.
[0075] From the perspective of achieving good shape stability of the second joint, especially the symmetry of the fishtail shape, the lower limit of the width of the grain is 35 nm or more, preferably 40 nm or more, 42 nm or more, or 44 nm or more, and more preferably 45 nm or more, 46 nm or more, 48 nm or more, 50 nm or more, 52 nm or more, 54 nm or more, or 55 nm or more. In particular, if the width of the grain is 45 nm or more, it is easy to achieve better symmetry of the fishtail shape and is preferred. In addition, the inventors have confirmed that if the width of the grain is within the above range, it is easy to achieve excellent bonding reliability of the second joint even in a severe high temperature environment.
[0076] The width of the grains on the surface of the line in condition (1) is obtained by analyzing the surface of the line by the electron backscattered diffraction (EBSD) method. The device used in the EBSD method is composed of a scanning electron microscope and a detector it has. The EBSD method is a method of projecting the diffraction pattern of reflected electrons generated when an electron beam is irradiated on a sample onto a detector, and determining the crystal orientation of each measurement point by analyzing the diffraction pattern. The data obtained by the EBSD method can be analyzed using the analysis software attached to the EBSD measurement device (such as OIM analysis manufactured by TSL solutions Co., Ltd.).
[0077] When the width of the grains on the surface of the wire is measured by the EBSD method, the position and size of the measurement surface are determined as follows. In addition, hereinafter, the width of the measurement surface refers to the size of the measurement surface in the direction perpendicular to the wire axis (the thickness direction of the wire, the circumferential direction of the wire), and the length of the measurement surface refers to the size of the measurement surface in the direction of the wire axis (the length direction of the wire, the length direction of the wire).
[0078] First, the bonding wire to be measured is fixed to the sample holder in a straight line. Next, the wire is positioned so that the center of the width of the wire in the direction perpendicular to the wire axis becomes the center of the width of the measuring surface, and the measuring surface is determined so that the width of the measuring surface is not less than 20% and not more than 40% of the wire diameter. The length of the measuring surface can be set to be 2 to 5 times the width of the measuring surface. By determining the position and size of the measuring surface as described above, the influence of the curvature of the wire surface can be suppressed, and it is possible to accurately measure and determine whether the condition (1) suitable for achieving good shape stability and bonding reliability of the second bonding portion is met. In addition, it is preferred to measure within a measurement magnification range of 5,000 to 20,000 times and a measurement point interval range of 0.02 to 0.05 μm.
[0079] Reference Figure 2 Further explanation. Figure 2 is a top view of line 1, with the line axis direction (line length direction) and Figure 2 The vertical direction (up and down direction) corresponds to the direction perpendicular to the line axis (the thickness direction of the line) and Figure 2 The horizontal direction (left and right direction) of Figure 2 In FIG. 1 , the measurement surface 2 is shown in relation to the line 1, but the width of the measurement surface 2 is the dimension w of the measurement surface in the direction perpendicular to the line axis. a The length of the measuring surface 2 is the dimension l of the measuring surface in the direction of the line axis. aIn addition, the meanings of "the width of the measurement surface" and "the length of the measurement surface" mentioned about the measurement surface are the same for the analysis based on AES in the condition (2) described later. Therefore, when performing the analysis using the EBSD method, the measurement surface 2 is positioned in such a way that the center of its width coincides with the single-point dashed line X which is the center of the width of the line, and the width w of the measurement surface is a The length of the measurement surface is determined to be 20% to 40% of the wire diameter (the same value as the wire width W), that is, 0.2W to 0.4W. a Meet 2w a ≦l a ≦5w a relationship.
[0080] When the width of the grains on the surface of the wire is measured by the EBSD method, in order to avoid the influence of dirt, attachments, bumps, scars, etc. on the surface of the wire, it is preferred to use only the crystal orientation that can be identified based on a certain reliability in the measurement surface, and exclude the parts where the crystal orientation cannot be measured, or even if the orientation analysis can be measured, the reliability is low. For example, when using OIM analysis made by TSL solutions as analysis software, it is preferred to exclude the measurement points with a CI value (Confidence Index) less than 0.1 for analysis. In addition, in the case where the excluded data exceeds 30% of the total, since there is a high possibility that the measurement object has some kind of contamination, it is preferred to implement it again from the preparation of the measurement sample. The so-called "grains on the surface of the wire" here is not only the grains exposed on the surface of the wire, but also a general term for grains identified as grains in EBSD measurement.
[0081] In addition, when the width of the grains on the surface of the line is measured by the EBSD method, it is preferred to regard the boundary with an orientation difference of 5 degrees or more between adjacent measurement points as a grain boundary to obtain the width of the grain. The calculation of the width of the grains on the surface of the line using the analysis software is generally performed by the following method: (i) drawing a line in the width direction of the measurement surface (circumferential direction of the line), and obtaining the size of each grain in the circumferential direction of the line according to the interval of the grain boundaries on the line, (ii) calculating the average size of the grain in the circumferential direction of the line by arithmetic averaging the size of each grain in the circumferential direction of the line. This method is implemented for a plurality of lines separated from each other in the length direction of the line (N number is preferably 10 or more, more preferably 20 or more), and the average value is used as the width of the grain.
[0082] The width of the crystal grains on the line surface in the condition (1) is based on the results measured under the conditions described in the column of "Crystal analysis of line surface by electron backscatter diffraction (EBSD) method" described later.
[0083] - Condition (2) -
[0084] Condition (2) relates to the composition of the region from the surface of the line to a depth of 10 nm in the concentration distribution in the depth direction of the line measured by AES (hereinafter also simply referred to as “concentration distribution in the depth direction”).
[0085] In combination with condition (1), by including a coating layer satisfying condition (2), the wire of the present invention can provide good shape stability of the second joint portion and good joint reliability of the second joint portion even in a severe high temperature environment.
[0086] The reason for such an effect is uncertain, but it is believed that in a Cu-based bonding wire having a coating layer containing three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag in a specific concentration range in the region from the surface to a depth of 10 nm, if the width of the grains on the surface of the wire is reduced to a certain range, the synergistic effect of the alloy composition and the fine grains on the surface can improve the sliding property between the splitter and the wire surface, suppress the damage of the coating layer, and achieve uniform compression deformation, improve the symmetry of the fishtail shape relative to the axis of the wire, and improve the dimensional stability of the fishtail shape. In addition, it is believed that through this effect, the damage of the coating layer is suppressed, the occurrence of corrosion in a high temperature environment can be suppressed, and the bonding reliability of the second bonding portion is improved. In this regard, it was confirmed that, represented by a coating layer containing only Pd, when the area from the surface to a depth of 10 nm contains two or less elements, or even if the area contains three or more elements, it does not contain three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag. Even if the width of the grain is reduced to a certain range, the shape stability and bonding reliability of the second bonding part (especially the shape stability of the second bonding part) will not improve. It was confirmed that the above-mentioned effect when the width of the grain is reduced to a certain range is specifically expressed in the Cu-based bonding wire having a coating layer with a specific surface composition.
[0087] In the present invention, when obtaining the concentration distribution of the wire in the depth direction by AES, it is preferably measured in a manner that the measurement points in the depth direction are more than 10 points and less than 20 points in the region from the surface of the wire to a depth of 10nm. Thus, it is possible to accurately measure and determine whether the condition (2) suitable for achieving good shape stability and bonding reliability of the second joint portion is established. Therefore, in a preferred embodiment, the coating layer of the wire of the present invention satisfies the above-mentioned condition (2) in the concentration distribution in the depth direction of the wire obtained by measuring the measurement points in the depth direction by AES in a region from the surface of the wire to a depth of 10nm and less than 10 points.
[0088] Regarding condition (2), from the viewpoint of achieving good shape stability of the second bonding portion, in particular, achieving a fishtail shape with small deviation in the deformation width in the direction perpendicular to the axis of the wire, the region from the surface of the wire to a depth of 10 nm (“region d 0-10 ”) contains three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag. The inventors have confirmed that in region d 0-10 The elements contained are two or less, or even if the area d 0-10 When three or more elements are contained but three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag are not contained, there is a tendency that the shape stability of the second bonding portion is deteriorated.
[0089] In addition, regarding condition (2), from the viewpoint of achieving good shape stability of the second joint portion, in particular, achieving a fishtail shape with small deviation in the deformation width in the direction perpendicular to the axis of the wire, the area d 0-10 The three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag contained in the above-mentioned alloy satisfy the following concentration conditions (i) and (ii):
[0090] (i) Regarding area d 0-10 At least three of the three or more elements contained in the region d 0-10 The average concentration of each element in the
[0091] (ii) Regarding area d 0-10 All of the three or more elements contained in the region d 0-10 The average concentration of each element in the carbon nanotubes is less than 80 atomic %.
[0092] Regarding concentration condition (i), regarding region d 0-10 At least three of the three or more elements contained in the region d 0-10 The average concentration of each element in the region d is 5 atomic % or more, preferably 6 atomic % or more or 8 atomic % or more, more preferably 10 atomic % or more, 12 atomic % or more, 14 atomic % or more or 15 atomic % or more. 0-10 At least three of the three or more elements contained in the region d 0-10 When the average concentration of each element in the wire is 10 atomic % or more, it is easy to achieve a fishtail shape with smaller deviation in the deformation width in the direction perpendicular to the axis of the wire, which is preferred. In addition, the inventors have confirmed that it is easy to achieve excellent bonding reliability of the second bonding portion even in a severe high temperature environment.
[0093] As mentioned above, regarding area d0-10 At least three of the three or more elements contained in the region d 0-10 It is important that the average concentration of each element in is 5 atomic % or more. As embodiments satisfying the concentration condition (i), the following (a) to (c) are mentioned, and the effects of the present invention can be enjoyed in any of the embodiments.
[0094] (a) Regarding area d 0-10 All the above three or more elements contained in the region d 0-10 The average concentration of each element in the mixture is 5 atomic % or more (the preferred range of the average concentration is as described above),
[0095] (b) Regarding area d 0-10 Three of the three or more elements contained in the region d 0-10 The average concentration of each element in the region is 5 atomic % or more (the preferred range of the average concentration is as described above), and with respect to the other one or two elements, the region d 0-10 The average concentration of each element in the
[0096] (c) Regarding area d 0-10 Four of the three or more elements contained in the region d 0-10 The average concentration of each element in the region is 5 atomic % or more (the preferred range of the average concentration is as described above), and for the other element, the region d 0-10 The average concentration of each element in the solution is less than 5 atomic %.
[0097] Here, (a) is in region d 0-10 (a) is a case where three to five elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag are contained, (b) is a case where four or five elements are contained, and (c) is a case where five elements are contained.
[0098] Regarding concentration condition (ii), regarding region d 0-10 All of the three or more elements contained in the region d 0-10 The average concentration of each element in the region d is 80 atomic % or less, preferably 75 atomic % or less, 74 atomic % or less, or 72 atomic % or less, and more preferably 70 atomic % or less, 68 atomic % or less, 66 atomic % or less, or 65 atomic % or less. 0-10 When the average concentration of each element in the wire is less than 70 atomic %, it is easy to achieve a fishtail shape with smaller deviation in the deformation width in the direction perpendicular to the axis of the wire, which is preferred. In addition, the inventors have confirmed that it is easy to achieve excellent bonding reliability of the second bonding portion even in a severe high temperature environment.
[0099] Region d in condition (2)0-10 The composition of can be confirmed and determined by the following method: while continuously digging downwards in the depth direction (toward the center of the wire) by Ar sputtering from the surface of the wire, a composition analysis is performed by AES. In detail, by repeatedly performing 1) composition analysis on the surface of the wire, 2) sputtering using Ar and 3) composition analysis on the surface after sputtering, the concentration change of each element in the depth (center) direction (the so-called concentration distribution in the depth direction) is obtained from the surface of the wire, and it can be confirmed and determined based on the concentration distribution. In the present invention, when obtaining the concentration distribution in the depth direction, the unit of depth is converted to SiO2. Here, when performing composition analysis by AES, gas components such as carbon (C), sulfur (S), oxygen (O), nitrogen (N), and non-metallic elements, etc. are not considered.
[0100] When performing 1) composition analysis of the line surface and 3) composition analysis of the surface after sputtering, the position and size of the measurement surface are determined as follows.
[0101] First, the bonding wire to be measured is fixed to the sample holder in a straight line. Next, the wire is positioned so that the center of the wire width in the direction perpendicular to the wire axis is the center of the width of the measurement surface, and the measurement surface is determined so that the width of the measurement surface is 5% to 15% of the wire diameter. The length of the measurement surface is set to be 5 times the width of the measurement surface. Figure 2 Further explanation. As mentioned above, Figure 2 In the figure, the width of the line is indicated by the reference symbol W, and the center of the width of the line is indicated by the dashed line X. Therefore, the measurement surface 2 is positioned so that the center of its width coincides with the dashed line X which is the center of the width of the line, and the width w of the measurement surface is a The length of the measurement surface is determined to be 5% to 15% of the wire diameter (the same value as the wire width W), that is, 0.05W to 0.15W. a Satisfy a =5w a By determining the position and size of the measuring surface as described above, it is possible to accurately determine whether the condition (2) suitable for achieving good shape stability and bonding reliability of the second bonding portion is satisfied.
[0102] In the present invention, when obtaining the concentration distribution in the depth direction of the line by composition analysis using AES, in order to improve the accuracy of the analysis, it is preferred to fix the peak values of each element used to detect Pd, Pt, Au, Ni, Ag, and Cu. That is, the energy value of the negative peak value (minimum value) of each element in the differential energy spectrum of Auger electrons (hereinafter referred to as "Auger electron spectrum") preferably uses the peak values of Au (2022eV), Pd (333eV), Pt (1969eV), Ag (359eV), Ni (849eV), and Cu (922eV) (source of energy values: built-in data of "MultiPak", an electronic spectroscopic spectrum analysis software manufactured by ULVAC-PHI).
[0103] When analyzing the Auger electron spectrum, the least squares method (Linear Least Squares: LLS processing) can be implemented as needed. Thereby, the element concentration can be quantified more accurately. For example, in the case where the energy values are close to each other and the peaks overlap, such as Cu and Ni, it is preferred to implement LLS processing when performing the process of separating the overlapping peak components. In addition, in the case where the influence of background noise is relatively high, such as when Au and Pt are contained in low concentrations, it is preferred to implement LLS processing in order to reduce the background noise. The analysis of the Auger electron spectrum can be implemented, for example, using the analysis software (MultiPak) installed in the AES device manufactured by ULVAC-PHI.
[0104] Next, in the obtained concentration distribution in the depth direction, we focus on the concentration C of Pd. Pd (atomic %), by comparing the area from the line surface position to the 10 nm depth position (i.e., area d 0-10 ) related to all the measurement points Pd The values of 0-10 Similarly, let’s focus on the Pt concentration C Pt (atomic %), by comparing with area d 0-10 All the measurement points related to C Pt The values of 0-10 The average concentration of Pt in the region d is the same as above. The average concentration of each element of Au, Ni, and Ag is also calculated by comparing the average concentration of each element with the region d. 0-10 The concentration values of each element related to all the measurement points are arithmetic averaged to obtain the area d 0-10 Then, in region d 0-10When the material contains three or more elements selected from Pd, Pt, Au, Ni, and Ag and satisfies the above-mentioned concentration conditions (i) and (ii), it is determined that condition (2) is satisfied. In addition, it is preferred to obtain the concentration distribution for a plurality of measurement surfaces (n≧3) separated from each other by more than 1 mm in the linear axis direction, and adopt the arithmetic mean value thereof.
[0105] The presence of each element and the average concentration thereof in the condition (2) are based on the results measured under the conditions described in the column of “Thickness analysis of coating layer by Auger electron spectroscopy (AES)” described later.
[0106] From the viewpoint of being able to enjoy the effect of the present invention more, the area d 0-10 The concentration of Pd C related to the measurement point Pd (atomic %), Pt concentration C Pt (atomic %), Au concentration C Au (atomic %), Ni concentration C Ni (atomic %), Ag concentration C Ag Total C (atomic %) Pd +C Pt +C Au +C Ni +C Ag The average value is preferably 70 atomic % or more, more preferably 80 atomic % or more, 85 atomic % or more or 90 atomic % or more, further preferably 92 atomic % or more, 94 atomic % or more, 95 atomic % or more, 96 atomic % or more, 98 atomic % or more or 99 atomic % or more, and the upper limit may be 100 atomic %.
[0107] The total C Pd +C Pt +C Au +C Ni +C Ag The average value of can be obtained by the following method: In the obtained depth direction concentration distribution, for area d 0-10 Total C related to all measurement points Pd +C Pt +C Au +C Ni +C Ag The values of are arithmetic average, or the area d obtained as described above is 0-10 The average concentration values of the elements Pd, Pt, Au, Ni, and Ag in the graphite are summed up.
[0108] - Other Preferred Conditions of the Coating Layer -
[0109] In the yarn of the present invention, the coating layer preferably satisfies one or both of the following conditions (3) and (4) in addition to satisfying the above conditions (1) and (2).
[0110] (3) The thickness of the coating layer is 40 nm to 200 nm.
[0111] (4) In the results of measuring the crystal orientation of the surface of the wire by the EBSD method, the crystal orientation in the wire length direction having an angle difference of 15 degrees or less with respect to the wire length direction <111> The ratio of the crystal orientation is 30% or more and 95% or less.
[0112] - Condition (3) -
[0113] Condition (3) relates to the thickness of the coating layer.
[0114] By including a coating layer that satisfies condition (3) in addition to conditions (1) and (2), the wire of the present invention can provide better bonding reliability of the second bonding portion even in a severe high-temperature environment.
[0115] Regarding condition (3), from the viewpoint of achieving good bonding reliability of the second bonding portion under high temperature environment, the thickness of the coating layer (the calculation method based on the concentration distribution in the depth direction of the line will be described later) is preferably 40nm or more, more preferably 42nm or more, 44nm or more, 45nm or more, 46nm or more, or 48nm or more, and further preferably 50nm or more, 55nm or more, 60nm or more, 65nm or more, or 70nm or more. The inventors have confirmed that in the combination of conditions (1) and (2), especially if the thickness of the coating layer is 50nm or more, it is easy to achieve a better bonding reliability of the second bonding portion even in a severe high temperature environment. In addition, from the viewpoint of achieving good bonding reliability of the second bonding portion under high temperature environment, the upper limit of the thickness of the coating layer is preferably 200nm or less, more preferably 10nm or less, 170nm or less, or 160nm or less, and further preferably 150nm or less, 140nm or less, 135nm or less, or 130nm or less. The present inventors have confirmed that, in the combination of conditions (1) and (2), particularly when the thickness of the coating layer is 150 nm or less, it is easy to achieve more excellent bonding reliability of the second bonding portion even in a severe high temperature environment.
[0116] The thickness of the coating layer is the same as described in connection with condition (2), and can be confirmed by the following method: while continuously digging downwards from the surface of the wire by Ar sputtering in the depth direction (toward the center of the wire), a composition analysis is performed by AES. In detail, by repeatedly performing 1) composition analysis of the surface of the wire, and then 2) sputtering using Ar and 3) composition analysis of the surface after sputtering, a concentration distribution in the depth direction is obtained, which can be confirmed based on the concentration distribution. The position and size of the measurement surface when performing composition analysis by AES are also the same as described in connection with condition (2). By determining the position and size of the measurement surface as described above, it is possible to accurately determine whether condition (3) suitable for achieving good bonding reliability of the second bonding portion is established.
[0117] The thickness of the coating layer can be determined based on the concentration distribution obtained in the depth direction. First, the boundary between the Cu core material and the coating layer is determined based on the concentration of Cu. The position where the Cu concentration is 50 atomic % is determined as the boundary, the area where the Cu concentration is more than 50 atomic % is the Cu core material, and the area less than 50 atomic % is the coating layer. In the present invention, the boundary between the Cu core material and the coating layer does not necessarily have to be a grain boundary. Then, the concentration distribution is confirmed from the wire surface to the wire center side, and it can be calculated as the distance from the wire surface position Z0 to the depth position Z1 where the concentration of Cu as the core material first reaches 50 atomic %. In the present invention, when determining the thickness of the coating layer based on the concentration distribution in the depth direction, the unit of depth is converted to SiO2. In addition, it is preferred to obtain the concentration distribution for multiple (n≧3) measurement surfaces separated by more than 1 mm in the wire axis direction, and adopt the arithmetic mean value thereof.
[0118] The thickness of the coating layer in the condition (3) is based on the result measured under the conditions described in the column of “Thickness analysis of coating layer by Auger electron spectroscopy (AES)” described later.
[0119] - Condition (4) -
[0120] Condition (4) refers to the condition that, in the result of measuring the crystal orientation of the surface of the wire by the EBSD method, the crystal orientation in the length direction of the wire has an angle difference of 15 degrees or less with respect to the length direction of the wire. <111> The ratio of crystal orientation (hereinafter referred to as “the ratio of the line surface <111> ratio of crystal orientations".).
[0121] As described above, the connection process using the bonding wire is completed by first bonding with the electrode on the semiconductor chip, and then, after forming a wire arc, the wire portion is secondly bonded to an external electrode such as an electrode on a lead frame or substrate. By including a coating layer that satisfies condition (4) in addition to conditions (1) and (2), a bonding wire that can stably form a desired wire arc shape can be realized.
[0122] Regarding condition (4), from the perspective of achieving a wire exhibiting good wire arc shape stability, the wire surface <111> The ratio of crystal orientation is preferably 30% or more, more preferably 35% or more, further preferably 40% or more, 45% or more, 50% or more, 55% or more, or 60%, and its upper limit is preferably 95% or less, more preferably 90% or less, further preferably 85% or less, 84% or less, 82% or less, or 80% or less. In particular, if the surface of the line <111> When the ratio of the crystal orientation is within a range of 40% to 85%, a bonding wire having particularly good arc shape stability can be realized.
[0123] Line surface <111> The ratio of crystal orientation is obtained by measuring the crystal orientation of the surface of the wire using the EBSD method. The device and analysis software used in the EBSD method are as described in connection with the above condition (1), and the surface of the wire is used as the measurement surface, and the position and size of the measurement surface are also as described above. Furthermore, when performing the analysis, only the crystal orientation identified based on a certain reliability is used in the measurement surface, and the calculation is performed excluding the parts where the crystal orientation cannot be measured, or the parts where the reliability of the orientation analysis is low even if it can be measured, as described in connection with the above condition (1). In the present invention, the surface of the wire <111> The ratio of the crystal orientation is preferably measured on a plurality of measurement surfaces (n≧3) separated from each other by 1 mm or more in the line length direction, and the arithmetic mean value thereof is adopted.
[0124] By adjusting the composition of the coating layer, the degree of wire drawing, heating conditions, etc., the surface <111> The ratio of the crystal orientation tends to be within a desired range. <111> The conditions of the crystal orientation ratio can be adjusted by, for example, increasing the processing rate, lowering the heating temperature, shortening the heating time, etc., in addition to adjusting the composition of the coating layer when the composition is the same.
[0125] The line surface in condition (4) <111> The ratio of the crystal orientation is based on the results measured under the conditions described in the column of “Line surface crystal analysis by electron backscatter diffraction (EBSD) method” described later.
[0126] The coating layer may contain, for example, one or more dopants selected from the first additional element, the second additional element, and the third additional element described below. Preferred contents of these dopants are described below.
[0127] In one embodiment, the coating layer is composed of three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, and inevitable impurities. In another embodiment, the coating layer is composed of three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, one or more elements selected from the first additional element, the second additional element, and the third additional element described later, and inevitable impurities. In addition, the term "inevitable impurities" for the coating layer also includes elements constituting the above-mentioned Cu core material.
[0128] As described above, the wire of the present invention including a coating layer satisfying conditions (1) and (2) can provide good shape stability of the second joint portion, and can also provide good bonding reliability of the second joint portion in a harsh high temperature environment. In the case of including a coating layer satisfying condition (3) in addition to these conditions (1) and (2), a wire that exhibits better bonding reliability of the second joint portion even in a harsh high temperature environment can be achieved. In addition, in the case of including a coating layer satisfying condition (4) in addition to these conditions (1) and (2), a wire that exhibits good wire arc shape stability can be achieved.
[0129] The wire of the present invention can achieve the desired effect regardless of the composition in the region exceeding 10 nm from the surface as long as the above conditions (1) and (2) are satisfied, and more preferably, as long as one or both of the above conditions (3) and (4) are satisfied in addition to the above conditions (1) and (2). In view of being able to enjoy the effect of the present invention more, in the concentration distribution in the depth direction of the wire, when the thickness of the coating layer is dt (nm), the total concentration of the element selected from the group consisting of Pd, Pt, Au, Ni, and Ag at the position of the depth dt (nm) from the wire surface, that is, at the boundary between the coating layer and the Cu core material, is preferably 35 atomic % or more, more preferably 40 atomic % or more, 42.5 atomic % or more, or 45 atomic % or more, further preferably 46 atomic % or more, 47 atomic % or more, 47.5 atomic % or more, 48 atomic % or more, 49 atomic % or more, or 49.5 atomic % or more, and the upper limit thereof may be 50 mass %. Similarly, from the viewpoint of being able to better enjoy the effects of the present invention, in the concentration distribution in the depth direction of the wire, when the thickness of the coating layer is set to dt (nm), at a depth of 0.5 dt (nm) from the surface of the wire, the total concentration of elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag is preferably 70 atomic % or more, more preferably 80 atomic % or more, 85 atomic % or more, or 90 atomic % or more, further preferably 92 atomic % or more, 94 atomic % or more, 95 atomic % or more, 96 atomic % or more, 98 atomic % or more, or 99 atomic % or more, and the upper limit may be 100 mass %.
[0130] From the viewpoint of achieving good shape stability of the second bonding portion and, further, from the viewpoint of achieving good bonding reliability of the second bonding portion even in a severe high temperature environment, an example of a concentration distribution in the depth direction of the wire of a particularly preferred embodiment is shown below.
[0131] Figure 3 This is a schematic diagram of the concentration distribution in the depth direction of a line obtained by measuring the line of one embodiment of the present invention by AES. Figure 3 In the concentration distribution in the depth direction shown, the change in concentration (mol% (atomic%); vertical axis) of the four elements A, B, C, and Cu is schematically shown in relation to the sputtering depth (nm; horizontal axis). Here, the A element, the B element, and the C element are elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag. Figure 3 In the concentration distribution in the depth direction shown, from the surface of the wire (the position of sputtering depth 0 nm) to a very shallow position (for example, when the thickness of the coating layer is set to dt, the depth is 0.3dt, 0.25dt, 0.2dt or 0.15dt), the concentration of element A decreases and the concentrations of element B and element C increase. When further advancing in the depth direction, up to a certain depth position (for example, when the thickness of the coating layer is set to dt, the depth is 0.9dt, 0.8dt, 0.7dt or 0.6dt), element B and element C coexist at a specified ratio. When further advancing in the depth direction, the concentrations of element B and element C decrease and the concentration of Cu increases. The wire having this concentration distribution in the depth direction can be formed, for example, by providing an alloy layer containing element B and element C at a specified ratio on a Cu core material, and further providing a layer of element A thereon.
[0132] Figure 4 This is a schematic diagram of the concentration distribution in the depth direction of a line obtained by measuring the line according to one embodiment of the present invention by AES. Figure 3 Likewise, in Figure 4 In the concentration distribution in the depth direction shown, the change in concentration (mol% (atomic%); vertical axis) of the four elements A, B, C and Cu with respect to the sputtering depth (nm; horizontal axis) is also schematically shown. Here, the A element, the B element, and the C element are elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag. Figure 4In the concentration distribution in the depth direction shown, from the surface of the wire (the position of sputtering depth 0 nm) to a very shallow position (for example, when the thickness of the coating layer is dt, the depth is 0.3dt, 0.25dt, 0.2dt, or 0.15dt), the concentration of element A decreases and the concentrations of elements B and C increase. When further advancing in the depth direction, the concentrations of elements B and C respectively become the maximum values, and then the concentrations of elements B and C decrease and the concentration of Cu increases. Element B can show the maximum concentration at a certain depth position (d1) or can show the maximum value within a certain depth range (d1 to d2). And element C can show the maximum concentration at a certain depth position (d3) or can show the maximum value within a certain depth range (d3 to d4). Here, d1, d2, d3, and d4 satisfy the relationship of d1 < d3 and d2 < d4. In addition, d1 can satisfy, for example, 0.05dt < d1 < 0.9dt, 0.1dt < d1 < 0.8dt, and d3 can satisfy, for example, 0.05dt < d3 < 0.9dt, 0.1dt < d3 < 0.8dt. A wire having such a concentration distribution in the depth direction can be formed, for example, by providing a layer of element C on a Cu core material, providing a layer of element B thereon, and further providing a layer of element A thereon.
[0133] Figure 5 is a schematic diagram of the concentration distribution in the depth direction of the wire of an embodiment of the present invention measured by AES. Similar to Figure 3 In the same way, in Figure 5 the concentration distribution in the depth direction shown, regarding the four elements of element A, element B, element C, and Cu, the change in concentration (mol% (atomic%); vertical axis) related to the sputtering depth (nm; horizontal axis) is also schematically shown. Here, element A, element B, and element C are respectively elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag. In Figure 5 the concentration distribution in the depth direction shown, from the surface of the wire (the position of sputtering depth 0 nm) to a certain depth position (for example, when the thickness of the coating layer is dt, the depth is 0.9dt, 0.8dt, 0.7dt, or 0.6dt), elements A, B, and C coexist at a specified ratio. When further advancing in the depth direction, the concentrations of elements A, B, and C decrease and the concentration of Cu increases. A wire having such a concentration distribution in the depth direction can be formed, for example, by providing an alloy layer containing elements A, B, and C at a specified ratio on a Cu core material.
[0134] Regarding the region d that the wire of the present invention should satisfy 0~10The composition in is as described in connection with condition (2), but from the viewpoint of being able to achieve good shape stability of the second bonding portion, and further, from the viewpoint of being able to achieve good bonding reliability of the second bonding portion even in a severe high temperature environment, the above Figure 3 to Figure 5 The A element in the concentration distribution in the depth direction shown is preferably selected from the group consisting of Au, Pd, and Ag. Figure 3 to Figure 5 The B element in the concentration distribution in the depth direction shown is preferably selected from the group consisting of Pd, Pt, Ni, and Ag, and the C element is preferably selected from the group consisting of Pd, Pt, and Ni. Therefore, in a preferred embodiment, the wire of the present invention contains an A element selected from the group consisting of Au, Pd, and Ag in the region from the surface to a depth of 10 nm in the concentration distribution in the depth direction of the wire, and further contains at least a B element selected from the group consisting of Pd, Pt, Ni, and Ag and a C element selected from the group consisting of Pd, Pt, and Ni (here, the A element, the B element, and the C element are mutually different elements.), and the average concentration of each of these A element, B element, and C element is in the range of 5 atomic % to 80 atomic %. Here, the preferred value of the lower limit of the average concentration of each element is as described in relation to the above-mentioned concentration condition (i), and the preferred value of the upper limit of the average concentration of each element is as described in relation to the above-mentioned concentration condition (ii). Among them, from the viewpoint of achieving better shape stability of the second bonding portion, and further, from the viewpoint of achieving better bonding reliability of the second bonding portion even in a severe high temperature environment, the wire of the present invention contains at least Au, Pd and Ni in the region from the surface to a depth of 10 nm in the concentration distribution in the depth direction of the wire, and the average concentration of each of these Au, Pd and Ni is within the range of 5 atomic % to 80 atomic %. In this embodiment, it is preferred that Au is contained as the A element, Pd or Ni is contained as the B element, and Ni or Pd is contained as the C element.
[0135] In addition, in the above Figure 3 to Figure 5 In the concentration distribution in the depth direction shown, the change in concentration related to the sputtering depth is shown for the four elements of element A, element B, element C and Cu, but the wire of the present invention may contain other elements (for example, elements other than element A to element C selected from the group consisting of Pd, Pt, Au, Ni, and Ag, the first additional element, the second additional element, the third additional element, etc. described later) as long as the above conditions (1) and (2) are satisfied. In the case where the wire contains elements other than element A, element B, element C and Cu, it is sufficient to determine whether condition (2) is satisfied by focusing on the concentration of the element selected from the group consisting of Pd, Pt, Au, Ni, and Ag.
[0136] The wire of the present invention may also contain one or more elements ("first additional element") selected from the group consisting of B, P, In and Mg. In the case where the wire of the present invention contains the first additional element, the total concentration of the first additional element relative to the entire wire is preferably 1 mass ppm or more. Thus, a bonding wire with a better crimping shape of the first bonding portion can be achieved. The total concentration of the first additional element relative to the entire wire is more preferably 2 mass ppm or more, further preferably 3 mass ppm or more, 5 mass ppm or more, 8 mass ppm or more, 10 ppm or more, 15 ppm or more or 20 mass ppm or more. From the viewpoint of suppressing the hardening of the wire and reducing chip damage during the first bonding, the total concentration of the first additional element is preferably 100 mass ppm or less, more preferably 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less or 50 mass ppm or less. Therefore, in a preferred embodiment, the wire of the present invention contains the first additional element, and the total concentration of the first additional element relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.
[0137] When the wire of the present invention contains the first additive element, the first additive element may be contained in either the Cu core material or the coating layer, or in both. From the viewpoint of realizing a bonding wire with a better crimping shape of the first bonding portion, it is preferred that the first additive element be contained in the Cu core material.
[0138] The wire of the present invention may also contain one or more elements ("second additional elements") selected from the group consisting of Se, Te, As and Sb. In the case where the wire of the present invention contains a second additional element, the total concentration of the second additional element relative to the entire wire is preferably 1 mass ppm or more. Thus, the bonding reliability of the first bonding portion under a high temperature and high humidity environment can be improved. The total concentration of the second additional element relative to the entire wire is more preferably 2 mass ppm or more, further preferably 3 mass ppm or more, 5 mass ppm or more, 8 mass ppm or more, 10 mass ppm or more, 15 mass ppm or more or 20 mass ppm or more. From the perspective of achieving a good crimping shape of the first bonding portion, the total concentration of the second additional element is preferably 100 mass ppm or less, more preferably 90 mass ppm or less, 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less or 50 mass ppm or less. Therefore, in a preferred embodiment, the wire of the present invention contains a second additional element, and the total concentration of the second additional element relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.
[0139] When the wire of the present invention contains the second additive element, the second additive element may be contained in either the Cu core material or the coating layer, or in both. From the viewpoint of realizing a bonding wire that provides better bonding reliability of the first bonding portion under a high temperature and high humidity environment, it is preferred that the second additive element be contained in the coating layer.
[0140] The wire of the present invention may also contain one or more elements selected from the group consisting of Ga, Ge and Ag ("third additional elements"). In the case where the wire of the present invention contains a third additional element, the total concentration of the third additional element relative to the entire wire is preferably 0.011 mass % or more. Thereby, the bonding reliability of the first bonding portion under a high temperature environment can be improved. The total concentration of the third additional element relative to the entire wire is more preferably 0.015 mass %, further preferably 0.02 mass %, 0.025 mass %, 0.03 mass %, 0.031 mass %, 0.035 mass %, 0.04 mass %, 0.05 mass %, 0.07 mass %, 0.09 mass %, 0.1 mass %, 0.12 mass %, 0.14 mass %, 0.15 mass % or more or 0.2 mass %. From the viewpoint of achieving a good crimping shape of the first joint portion and achieving good bonding properties of the second joint portion, the total concentration of the third additional element is preferably 1.5 mass % or less, more preferably 1.4 mass % or less, 1.3 mass % or less, or 1.2 mass % or less. Therefore, in a preferred embodiment, the wire of the present invention contains the third additional element, and the total concentration of the third additional element relative to the entire wire is 0.011 mass % or more and 1.5 mass % or less.
[0141] When the wire of the present invention contains the third additional element, the third additional element may be contained in either one of the Cu core material and the coating layer, or may be contained in both.
[0142] The contents of the first additional element, the second additional element, and the third additional element in the wire can be measured by the method described in [Measurement of Element Content] described later.
[0143] The diameter of the wire of the present invention is not particularly limited and can be appropriately determined according to the specific purpose. The lower limit of the diameter can be, for example, 15 μm or more, 16 μm or more, and the upper limit of the diameter can be, for example, 80 μm or less, 70 μm or less, or 50 μm or less.
[0144] <Method for producing thread>
[0145] An example of the method for producing the bonding wire for a semiconductor device of the present invention will be described.
[0146] First, raw copper with high purity (4N to 6N: 99.99 to 99.9999% by mass or more) is processed into a large diameter (about 3 to 7 mm in diameter) by continuous casting to obtain an ingot.
[0147] When adding dopants such as the first additional element, the second additional element, and the third additional element, as the method of adding them, for example, there can be cited a method of containing them in the Cu core material, a method of containing them in the coating layer, a method of coating the surface of the Cu core material, and a method of coating the surface of the coating layer, and these methods can also be combined in multiple ways. Regardless of which adding method is adopted, the effect of the present invention can be exerted. In the method of making the Cu core material contain a dopant, a copper alloy containing a dopant of the desired concentration can be used as a raw material to manufacture the Cu core material. In the case of adding a dopant to Cu as a raw material to obtain the copper alloy, a high-purity dopant component can be directly added to Cu, or a master alloy containing a dopant component of about 1% can be used. In the method of making the coating layer contain a dopant, the dopant can be contained in the Pd, Pt, Au, Ni, Ag plating bath (in the case of wet plating) or the target (in the case of dry plating) when forming the coating. In the method of coating the surface of a Cu core material or the method of coating the surface of a coating layer, the surface of the Cu core material or the surface of the coating layer is used as the coating surface, and the following steps (1) are performed: The coating treatment may be one or more selected from (2) plating method (wet method) and (3) vapor deposition method (dry method).
[0148] The large-diameter ingot is forged, rolled, and drawn to produce a wire (hereinafter also referred to as an "intermediate wire") made of Cu or a Cu alloy having a diameter of about 0.7 to 2.0 mm.
[0149] As a method for forming a coating layer on the surface of the Cu core material, electroplating, electroless plating, evaporation method, etc. can be used, but electroplating that can stably control the film thickness is preferably used in industry. For example, a coating layer can be formed on the surface of a large-diameter ingot, a coating layer can be formed on the surface of an intermediate wire, or a coating layer can be formed on the surface of the Cu core material after the intermediate wire is further thinned by wire drawing (for example, after drawing to the final diameter of the Cu core material). Among them, in order to easily adjust the width of the grains on the surface of the wire in the above condition (1) to the desired range, the coating layer is preferably formed at the stage where the Cu core material is 50 to 500 times the final wire diameter, and the coating layer is preferably formed on the surface of a large-diameter ingot. This is because, by forming a coating layer at the stage where the Cu core material is large in diameter, the degree of processing of the coating layer can be improved in subsequent wire drawing processing, etc., and it is easy to refine the grains at the final wire diameter.
[0150] As described above, the coating layer can be formed, for example, by providing an alloy layer containing B element and C element at a prescribed ratio on the surface of the Cu core material, and further providing a layer of A element thereon (hereinafter, also referred to as "two-stage coating"). In addition, the coating layer can be formed, for example, by providing a layer of C element on the surface of the Cu core material, and providing a layer of B element thereon, and further providing a layer of A element thereon (hereinafter, also referred to as "three-stage coating"). Furthermore, the coating layer can be formed, for example, by providing an alloy layer containing A element, B element and C element at a prescribed ratio on the surface of the Cu core material (hereinafter, also referred to as "one-stage coating"). The following shows an example of the steps for forming the coating layer by two-stage coating using Au as the A element, Pd and Ni as the B element and the C element. That is, the coating layer can be formed, for example, by providing a PdNi alloy layer containing Pd and Ni at a prescribed ratio on the surface of the Cu core material, and providing an Au layer thereon. Here, from the viewpoint of forming a coating layer with excellent adhesion to the Cu core material, after impact plating of a conductive metal is performed on the surface of the Cu core material, a PdNi alloy layer containing Pd and Ni at a specified ratio can be provided. In addition, the coating step can be appropriately adjusted, such as after forming a PdNi alloy layer containing Pd and Ni at a specified ratio, further providing one or more layers containing Pd and Ni (for example, a Pd layer, a Ni layer, a PdNi alloy layer), and then providing an Au layer thereon.
[0151] The wire drawing process can be implemented using a continuous wire drawing device that can be provided with multiple diamond-coated dies. As required, heat treatment can also be implemented in the middle stage of the wire drawing process. By heat treatment, the constituent elements of the coating layer are mutually diffused, and a region (for example, an alloy region containing Au, Pd and Ni) containing three or more elements selected from the group consisting of Pd, Pt, Au, Ni and Ag can be formed near the surface of the wire in a prescribed concentration in a manner that satisfies the above-mentioned condition (2). As a method thereof, a method of promoting alloying by continuously sweeping the wire at a certain speed in an electric furnace at a certain furnace temperature can reliably control the composition and thickness of the alloy, so it is preferred.
[0152] In the following, with regard to an embodiment of forming a coating layer on the surface of a Cu core material by electroplating, a preferred embodiment is described from the viewpoint of adjusting the width of the crystal grains on the surface of the wire in the above condition (1) to a desired range.
[0153] In this preferred embodiment, the conditions of electroplating, wire drawing, and heat treatment are controlled to adjust the width of the grains on the wire surface to a desired range.
[0154] First, in the electroplating process, in order to induce the nucleation of the constituent elements of the coating layer and suppress the growth of crystal grains, the temperature of the plating bath is preferably a low temperature below 60°C, more preferably below 50°C. The lower limit of the temperature of the plating bath is not particularly limited as long as the electroplating can be smoothly implemented, for example, it can be set to above 10°C, above 15°C, above 20°C, etc. In the electroplating process, in order to induce the nucleation of the constituent elements of the coating layer and suppress the growth of crystal grains, it is preferred to stir the plating solution and implement the plating treatment in a liquid flowing state. Therefore, in a preferred embodiment, in the electroplating process, the plating treatment is implemented using a plating bath at 10 to 60°C (more preferably 10 to 50°C) in a liquid flowing state.
[0155] In addition, regarding wire drawing and heat treatment, it is preferred to perform intermediate heat treatment during wire drawing when the wire diameter is in the range of 5 to 50 times the final wire diameter. This is because by performing appropriate intermediate heat treatment, it is easy to adjust the processing strain inside the coating layer, thereby adjusting the size of the grains under the final wire diameter. In addition, this is because by performing appropriate intermediate heat treatment, the constituent elements of the coating layer diffuse and alloy with each other, thereby delaying recrystallization and making it easy to refine the size of the grains.
[0156] In particular, in a preferred embodiment, when the Cu core material has a large diameter of 50 to 500 times the final wire diameter, an electroplating treatment is performed using a plating bath at 10 to 60° C. in a liquid flowing state to form a coating layer on the surface of the Cu core material. Further, the wire is subjected to wire drawing, and preferably an intermediate heat treatment is performed during the wire drawing process when the wire diameter is in the range of 5 to 50 times the final wire diameter.
[0157] The wire of the present invention can bring about good shape stability of the second bonding portion. Moreover, the wire of the present invention can bring about good bonding reliability of the second bonding portion even in a harsh high temperature environment. Therefore, the bonding wire of the present invention is suitable for use as various bonding wires, represented by bonding wires for vehicle-mounted devices or power devices.
[0158] [Method for manufacturing semiconductor device]
[0159] A semiconductor device can be manufactured by connecting electrodes on a semiconductor chip and external electrodes such as electrodes on a lead frame or a circuit board using the bonding wire for a semiconductor device of the present invention.
[0160] In one embodiment, a semiconductor device of the present invention includes a circuit substrate, a semiconductor chip, and a bonding wire for electrically connecting the circuit substrate and the semiconductor chip, wherein the bonding wire is the wire of the present invention.
[0161] In the semiconductor device of the present invention, the circuit substrate and the semiconductor chip are not particularly limited, and known circuit substrates and semiconductor chips that can be used to constitute a semiconductor device can be used. Alternatively, a lead frame can be used instead of a circuit substrate. For example, as in the semiconductor device described in Japanese Patent Publication No. 2020-150116, the structure of the semiconductor device can also be a semiconductor device including a lead frame and a semiconductor chip mounted on the lead frame.
[0162] Examples of semiconductor devices include various semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, televisions, air conditioners, solar power generation systems, etc.) and vehicles (e.g., motorcycles, cars, trains, ships, airplanes, etc.).
[0163] [Example]
[0164] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited to the examples described below.
[0165] (sample)
[0166] First, the method for preparing the sample is described. The raw material of the Cu core material is a raw material having a purity of 99.99 mass % or more (4N) and the remainder consisting of inevitable impurities. In addition, when the first additional element, the second additional element, and the third additional element are added, these raw materials having a purity of 99 mass % or more and the remainder consisting of inevitable impurities are used, or a master alloy in which these additional elements are mixed with Cu at a high concentration is used.
[0167] The raw materials of the core Cu alloy are first loaded into a graphite crucible, and then heated to 1090-1500°C in an inert atmosphere such as N2 gas and Ar gas using a high-frequency furnace to melt, and then an ingot with a diameter of 4-7 mm is produced by continuous casting. Next, a coating layer is formed on the obtained ingot by electroplating. Regarding the formation of the coating layer, in order to remove the oxide film on the surface of the ingot, a pickling treatment using hydrochloric acid or sulfuric acid is carried out, and then it is implemented by two-stage coating (for example, Examples No. 1, 2, 4, 5, etc.), three-stage coating (for example, Examples No. 3, 6, 10, etc.), and one-stage coating (for example, Examples No. 7, 12, 13, etc.). In detail, in the embodiments No. 1, 2, 4, 5, etc. based on two-stage coating, a plating solution of a PtNi alloy containing Pt and Ni at a specified ratio or a plating solution of a PdNi alloy containing Pd and Ni at a specified ratio is used to form a PtNi alloy layer or a PdNi alloy layer in a manner that covers the entire surface of the ingot, and an Au plating solution is further used to set an Au layer on the PtNi alloy layer or the PdNi alloy layer. In addition, in the embodiments No. 3, 6, 10, etc. based on three-stage coating, a plating solution of Pd, Pt or Ni is used to set a Pd layer, a Pt layer or a Ni layer (first layer) in a manner that covers the entire surface of the ingot, and a plating solution of Pd, Pt or Ni is further used to set a Pd layer, a Pt layer or a Ni layer (second layer; different from the first layer) on the first layer, and an Ag layer or an Au layer (third layer) is further used to set an Ag or Au plating solution on the second layer. In addition, in the embodiments No. 7, 12, 13, etc. based on the one-stage coating, a plating solution of a PtNiAg alloy containing Pt, Ni, and Ag at a predetermined ratio, a plating solution of an AuPdNi alloy containing Au, Pd, and Ni at a predetermined ratio, or a plating solution of an AuPtNi alloy containing Au, Pt, and Ni at a predetermined ratio is used to set a PtNiAg alloy layer, an AuPdNi alloy layer, or an AuPtNi alloy layer in a manner covering the entire surface of the ingot. In addition, the formation of each layer by the electroplating method is performed by setting the plating bath temperature to 20 to 40° C., and stirring the plating solution while the liquid is flowing.
[0168] After that, stretching, wire drawing, etc. are performed to the final wire diameter. In order to control the width of the grains near the surface of the wire, 1 to 2 intermediate heat treatments are performed during the processing as needed. The conditions for the intermediate heat treatment are to set the heat treatment temperature to 200 to 600°C when the wire diameter is 0.1 to 0.3 mm, and the heat treatment time to 1 to 6 seconds. In addition, when performing the intermediate heat treatment, the wire is continuously swept while N2 gas or Ar gas is flowing. After processing to the final wire diameter, the wire is continuously swept while N2 or Ar gas is flowing while tempering heat treatment is performed. The heat treatment temperature of the tempering heat treatment is set to 200 to 600°C, the wire conveying speed is set to 20 to 200 m / min, and the heat treatment time is set to 0.2 to 0.8 seconds. In the case of reducing the width of the grains, the heat treatment temperature is lowered, or the wire conveying speed is set to be fast, and in the case of increasing the width of the grains, the heat treatment temperature is increased, or the wire conveying speed is set to be slow.
[0169] (Test and evaluation methods)
[0170] The test and evaluation methods are described below.
[0171] [Thickness analysis of coating layer using Auger electron spectroscopy (AES)]
[0172] The thickness of the coating layer was analyzed using depth analysis using AES. Depth analysis using AES is to analyze the composition changes in the depth direction by alternately performing composition analysis and sputtering, and can obtain the concentration changes of each element in the depth (center) direction from the line surface (the so-called concentration distribution in the depth direction).
[0173] First, the bonding wire to be measured is fixed to the sample holder in a straight line. Then, by AES, 1) composition analysis of the wire surface is repeated, followed by 2) sputtering with Ar and 3) composition analysis of the surface after sputtering to obtain the concentration distribution in the depth direction. + ions and an accelerating voltage of 2kV. In addition, in the composition analysis of the surface 1) and 3), the size of the measuring surface or the conditions for the composition analysis using AES are as follows. That is, the positioning is performed in such a way that the center of the width of the line in the direction perpendicular to the line axis becomes the center of the width of the measuring surface, and the measuring surface is determined in such a way that the width of the measuring surface is greater than 5% and less than 15% of the line diameter. The length of the measuring surface is set to 5 times the width of the measuring surface. Then, using an AES device (PHI-700 manufactured by ULVAC-PHI), a composition analysis of the surface of the line is performed under an accelerating voltage of 10Kv to determine the concentration (atomic %) of each element of Pd, Pt, Au, Ni, Ag, and Cu. When determining the concentration of each element, gas components such as carbon (C), sulfur (S), oxygen (O), and nitrogen (N), non-metallic elements, etc. are not considered.
[0174] When the concentration distribution in the depth direction is obtained by depth analysis using AES, the peak values for detecting each element of Pd, Pt, Au, Ni, Ag, and Cu are as follows. That is, focusing on the energy value of the negative peak (minimum value) of each element in the Auger electron spectrum, the peak values of Au (2022 eV), Pd (333 eV), Pt (1969 eV), Ag (359 eV), Ni (849 eV), and Cu (922 eV) are used.
[0175] In addition, using the analysis software (PHI MultiPak) installed in the AES device, the analysis of the Auger electron spectrum and the calculation of the concentration are performed. In order to improve the accuracy of the analysis, LLS processing is implemented as needed. In detail, for the object sample (line) having a part containing both Cu and Ni, LLS processing is implemented when the peaks of Cu and Ni are separated. That is, when the object sample is analyzed, pure Cu and pure Ni are used to obtain the Auger electron spectrum, and the spectrum is used as the data of the reference sample of the element to implement LLS processing. In addition, in the object sample, when the part containing Cu but not containing Ni (containing the Cu part) and the part containing Ni but not containing Cu (containing the Ni part) are separately present, the Auger electron spectrum containing the Cu part and the Auger electron spectrum containing the Ni part are used as the data of the reference sample of the element, and LLS processing is implemented in the concentration analysis of the Ni element and the Cu element. In addition, for the object sample containing Au or Pt, LLS processing is implemented in order to reduce background noise. At this time, the waveform of the Auger electron spectrum near the above-mentioned peak energy value of Au or Pt in the Auger electron spectrum is used as a benchmark for LLS processing.
[0176] Furthermore, the concentration distribution in the depth direction was obtained for three measurement surfaces that were separated from each other by 1 mm or more in the line length direction.
[0177] - Region d from the surface to a depth of 10 nm 0-10 The average concentration of each element in
[0178] When obtaining the concentration distribution in the depth direction by AES, the measurement point in the depth direction is in the area d 0-10 The depth of the sputtering speed is measured in a manner of more than 10 points and less than 20 points. In addition, the depth measured by AES analysis is obtained as the product of the sputtering speed and the time. Generally speaking, since the sputtering speed is measured using SiO2 as a standard sample, the depth analyzed by AES is a SiO2 conversion value. That is, the unit of the thickness of the coating layer uses a SiO2 conversion value. It is set to be based on this SiO2 conversion value, and the measurement points are equally spaced.
[0179] Next, in the obtained depth-direction concentration distribution, we focus on the Pd concentration CPd (atomic %), by comparing the area from the line surface position to the 10 nm depth position (i.e., area d 0-10 ) related to all the measurement points Pd The area d is obtained by taking the arithmetic mean of the values 0-10 The average concentration of Pd in the region d is the same as above. 0-10 The concentration of each element at all measurement points was calculated by taking the arithmetic average.
[0180] Area D 0-10 The average concentration of each element in the graph is the arithmetic mean of the values obtained for the three measurement surfaces.
[0181] -Thickness of coating layer-
[0182] In the obtained concentration distribution in the depth direction, the concentration distribution is confirmed from the line surface to the line center side, and the distance Z1 from the line surface position Z0 to the depth position where the concentration of Cu as the core material first reaches 50 atomic % is obtained as the measured coating layer thickness. The arithmetic mean of the values obtained for the three measurement surfaces is used as the thickness of the coating layer. In addition, for the wire of the example, the total number of measurement points for the coating layer is confirmed to be 50 to 100 points.
[0183] In addition, regarding the wire of the example, it was confirmed that in the concentration distribution in the depth direction of the wire, when the thickness of the coating layer was set to dt, the total concentration of the element selected from the group consisting of Pd, Pt, Au, Ni, and Ag at the position of the depth dt from the wire surface, that is, at the boundary between the coating layer and the Cu core material, was 45 atomic % or more. In addition, regarding the wire of the example, it was confirmed that in the concentration distribution in the depth direction of the wire, when the thickness of the coating layer was set to dt, the total concentration of the element selected from the group consisting of Pd, Pt, Au, Ni, and Ag at the position of the depth 0.5 dt from the wire surface was 90 atomic % or more.
[0184] [Crystal analysis of line surfaces using the electron backscatter diffraction (EBSD) method]
[0185] The crystal analysis of the wire surface was performed by the EBSD method using the wire surface as the measurement surface.
[0186] - Width of grains on the wire surface -
[0187] First, the bonding wire to be measured is fixed to the sample holder in a straight line. Next, the center of the width of the wire in the direction perpendicular to the wire axis (circumferential direction of the wire) is positioned in a manner that becomes the center of the width of the measurement surface, and the measurement surface is determined in a manner that the width of the measurement surface is 7 μm and the length of the measurement surface is 15 μm. Then, an EBSD measurement device (SU-70 manufactured by Hitachi High-Technologies) is used to measure at a measurement magnification of 15,000 times and a measurement point interval of 0.03 μm. During the measurement, the acceleration voltage is appropriated in the range of 15 to 30 kV according to the surface state of the sample. Next, the analysis software (OIM analysis manufactured by TSL Solutions) attached to the EBSD measuring device was used to remove the measurement points with a CI value (Confidence Index) less than 0.1 for analysis, and the boundaries with an orientation difference of 5 degrees or more between adjacent measurement points were regarded as grain boundaries. The lower limit number of pixels or the number of pixels identified as grains (in the setting of the device attached software, the minimum size of the item equivalent to the grain size) was set to a value of 2 to 5, and the average size of the grains in the linear circumferential direction, that is, the width (nm) of the grains was obtained. When analyzing, the crystal data of the element with the highest average concentration in the coating layer was used.
[0188] In addition, the calculation of the width of the grains on the line surface using the analysis software is performed by the following method: (i) a line is drawn in the width direction (circumferential direction of the line) of the measurement surface, and the size of each grain in the circumferential direction of the line is calculated based on the interval of the grain boundary on the line, and (ii) the size of each grain in the circumferential direction of the line is arithmetic averaged to calculate the average size of the grain in the circumferential direction of the line. This is performed on a plurality of lines (N=20 to 50) separated from each other in the length direction of the line, and the average value is used. In addition, in the analysis software, if the number of lines N is set, the lines are automatically set at equal intervals.
[0189] - Crystal orientation of the wire surface -
[0190] In the same manner as above, the bonding wire to be measured is fixed to the sample holder, and after the measurement surface is determined, the crystal orientation of the measurement surface is observed, and the crystal orientation in the wire length direction with an angle difference of 15 degrees or less relative to the wire length direction is obtained. <111> The ratio of crystal orientation.
[0191] The crystal orientation was measured by the EBSD method on three measurement surfaces separated from each other by 1 mm or more in the line length direction, and the average value thereof was adopted.
[0192] [Determination of element content]
[0193] The contents of the first additional element, the second additional element, and the third additional element in the wire are detected as the concentrations of the elements contained in the entire wire by analyzing the liquid obtained by dissolving the bonding wire with a strong acid using an ICP emission spectrometer or an ICP mass spectrometer. As the analysis device, an ICP-OES ("PS3520UVDDII" manufactured by Hitachi High-Tech Science Co., Ltd.) or an ICP-MS ("Agilent 7700x ICP-MS" manufactured by Agilent Technologies Co., Ltd.) is used.
[0194] [Shape stability of the second joining portion]
[0195] The lead frame lead portion was wedge bonded using a commercially available wire bonding machine to produce a sample for evaluating the shape stability of the second bonded portion. The lead frame was a Fe-42 atomic % Ni alloy lead frame with 1 to 3 μm Ag plating, and the bonding was performed at a table temperature of 200° C. and a flow of 0.5 L / min of N2+5% H2 gas.
[0196] -Joint shape (symmetry of fishtail shape)-
[0197] Regarding the joining shape of the second joining portion, 2000 second joining portions randomly selected from the samples for evaluating the shape stability of the second joining portion were observed to evaluate the symmetry of the fishtail shape. Specifically, the portions where the fishtail shape was asymmetric or curled relative to the axis of the wire were counted as defective portions and evaluated according to the following criteria.
[0198] Evaluation criteria:
[0199] ◎◎: There are less than 1 defective part
[0200] ◎: There are 2 or more but less than 4 defective parts
[0201] ○: The number of defective parts is 5 or more but less than 9
[0202] ×: There are 10 or more defective parts
[0203] -Joint width (stability of the deformation width of the fishtail shape)-
[0204] Regarding the joining width of the second joining portion, 2000 second joining portions randomly selected from the samples for evaluating the shape stability of the second joining portion were observed, the standard deviation of the fishtail shape deformation width in the direction perpendicular to the axis of the wire was calculated, and evaluation was performed according to the following criteria.
[0205] Evaluation criteria:
[0206] ◎: 3σ less than 5μm
[0207] ○: 3σ is 5 μm or more and less than 15 μm
[0208] ×: 3σ is 15 μm or more
[0209] [Joining Reliability of Second Joining Section]
[0210] The bonding reliability of the second bonding portion was evaluated by a high temperature storage life test (HTSL: High Temperature Storage Life Test).
[0211] The sample formed by wedge bonding on the pin part of the lead frame using a commercially available wire bonding machine was sealed with a commercially available thermosetting epoxy resin to prepare a sample for the bonding reliability test of the second joint. The lead frame used a Fe-42 atomic % Ni alloy lead frame with 1 to 3 μm Ag plating, and was bonded at a table temperature of 200°C and N2+5% H2 gas flow of 0.5 L / min. The sample for the bonding reliability test of the second joint was exposed to a high temperature environment of 180°C using a high temperature thermostat. The bonding life of the second joint is the time when the tensile test of the wedge joint is carried out every 500 hours and the value of the tensile strength becomes 1 / 2 of the initial tensile strength. The value of the tensile strength uses the arithmetic mean of the measured values at 50 randomly selected wedge joints. The tensile test after the high temperature placement test is carried out after the resin is removed by acid treatment to expose the wedge joint. Then, it is evaluated according to the following criteria.
[0212] Evaluation criteria:
[0213] ◎◎: Bonding life more than 2000 hours
[0214] ◎: Bonding life is more than 1000 hours and less than 2000 hours
[0215] ○: Bonding life is 500 hours or more and less than 1000 hours
[0216] ×: Bonding life is less than 500 hours
[0217] [Joining Reliability of First Joining Section]
[0218] The bonding reliability of the first bonding portion was evaluated by both a high temperature and high humidity test (HAST: Highly Accelerated Temperature and Humidity Stress Test) and a high temperature storage life test (HTSL: High Temperature Storage Life Test).
[0219] -HAST-
[0220] The samples were made by ball bonding electrodes formed of an alloy of Al-1.0 mass% Si-0.5 mass% Cu with a film thickness of 1.5 μm on a silicon substrate on a general metal frame using a commercially available wire bonding machine, and sealed with a commercially available thermosetting epoxy resin to prepare the samples for the first joint reliability test. The balls were formed while flowing N2+5% H2 gas at a flow rate of 0.4 to 0.6 L / min, with the current value set to 30 to 75 mA, the gap of the EFO set to 762 μm, and the tail length set to 254 μm. The diameter was set to a range of 1.5 to 1.9 times the wire diameter. The samples for the evaluation of the joint reliability of the first joint prepared were exposed to a high temperature and high humidity environment of 130°C and 85% relative humidity using an unsaturated pressure cooker tester, and a bias voltage of 7 V was applied. The joint life of the first joint was set to the time when the shear strength value of the ball joint was 1 / 2 of the initial shear strength obtained by performing a shear test of the ball joint every 48 hours. The shear strength value was the arithmetic mean of the measured values at 50 randomly selected ball joints. The shear test was performed after the resin was removed by acid treatment to expose the ball joints. Then, the evaluation was performed according to the following criteria.
[0221] Evaluation criteria:
[0222] ◎: Joint life more than 384 hours
[0223] ○: Bonding life 240 hours or more and less than 384 hours
[0224] ×: Bonding life is less than 240 hours
[0225] -HTSL-
[0226] The sample for evaluating the reliability of the first joint made in the same steps as above was exposed to an environment of 175°C using a high temperature thermostat. The joint life of the first joint is set to the time when the shear test of the ball joint is carried out every 500 hours and the shear strength value becomes 1 / 2 of the initial shear strength. The shear strength value uses the arithmetic mean of the measured values at 50 randomly selected ball joints. The shear test after the high temperature placement test is carried out after the resin is removed by acid treatment to expose the ball joint. Then, the evaluation is carried out according to the following criteria.
[0227] Evaluation criteria:
[0228] ◎: Bonding life more than 2000 hours
[0229] ○: Bonding life is 1000 hours or more and less than 2000 hours
[0230] ×: Bonding life is less than 1000 hours
[0231] [Arc shape]
[0232] The shape stability of the wire loop (reproducibility of the wire loop profile) was evaluated based on the standard deviation of the maximum wire loop height by connecting 30 trapezoidal wire loops with a wire loop length of 2 mm, a height difference of 250 μm at the joint, and a wire loop height of 200 μm. The height was measured using an optical microscope and evaluated according to the following criteria.
[0233] Evaluation criteria:
[0234] ◎: 3σ less than 20μm
[0235] ○: 3σ is 20 μm or more and less than 30 μm
[0236] ×: 3σ is 30 μm or more
[0237] [Crimp shape]
[0238] The evaluation of the crimping shape of the first joint (the flattened shape of the ball) is performed as follows: a ball is formed under the conditions described in the above [Joint reliability of the first joint] column using a commercially available wire bonding machine, and the ball is crimped and bonded to an electrode of an alloy of Al-1.0 mass% Si-0.5 mass% Cu formed on a Si substrate and provided with a thickness of 1.5 μm, and observed from directly above using an optical microscope (evaluation number N = 100). In the determination of the flattened shape of the ball, it is judged to be good if the flattened shape is close to a perfect circle, and it is judged to be poor if it is an elliptical or petal-shaped shape. Then, the evaluation is performed according to the following criteria.
[0239] Evaluation criteria:
[0240] ◎: No defect
[0241] ○: 1 to 3 defects (no problem in practical use)
[0242] △: 4 to 5 defects (no problem in practical use)
[0243] ×: More than 6 defects
[0244] [Chip damage]
[0245] The chip damage was evaluated as follows: a ball was formed under the conditions described in the [Joint reliability of the first joint] column using a commercially available wire bonding machine, and the ball was crimped and bonded to an electrode formed on a Si substrate and provided with an Al-1.0 mass % Si-0.5 mass % Cu alloy having a thickness of 1.5 μm, and then the wire and the electrode were dissolved using a chemical solution to expose the Si substrate, and the Si substrate directly below the joint was observed using an optical microscope (evaluation number N = 50). Then, the evaluation was performed according to the following criteria.
[0246] Evaluation criteria:
[0247] ◎: No cracks or joint marks
[0248] ○: There are no cracks but there are places where traces of joining can be confirmed (3 or less places)
[0249] ×: Other than the above
[0250] The evaluation results of Examples and Comparative Examples are shown in Tables 1 and 2.
[0251] [Table 1]
[0252]
[0253] [Table 2]
[0254]
[0255] It was confirmed that the wires of Examples No. 1 to 36 all have coating layers that satisfy the specific conditions (1) and (2) of the present invention, and that the fishtail shape has good symmetry and can achieve a fishtail shape with small deviation in the deformation width in the direction perpendicular to the axis of the wire, and provide good shape stability of the second joint. It was also confirmed that the second joint has good bonding reliability even in a severe high temperature environment of 180°C.
[0256] Furthermore, the wires of Examples Nos. 1 to 13 and 15 to 36 in which the thickness of the coating layer is 40 nm to 200 nm, and in which the thickness is in the preferred range of 50 nm to 150 nm, tend to exhibit particularly good bonding reliability of the second bonding portion in a severe high temperature environment.
[0257] Furthermore, in the results of measuring the crystal orientation of the surface of the wire by the EBSD method, it was confirmed that the crystal orientation in the wire length direction had an angle difference of 15 degrees or less with respect to the wire length direction. <111> The wires of Examples No. 1 to 3, 5 to 27, and 29 to 36, in which the ratio of the crystal orientation was 30% to 95%, all had good wire arc shapes. <111> The wires of Examples Nos. 2, 3, 5 to 10, 12, 16 to 21, 23 to 27, 30 to 33, and 36, in which the ratio of the crystal orientation is within the preferred range of 40% to 85%, are likely to achieve a better wire arc shape.
[0258] In addition, it was confirmed that the wires of Examples No. 15 to 19, 25, 26, 32, 33, 35, and 36 containing 1 mass ppm or more of the first additive element in total brought a better crimping shape of the first joint. It was confirmed that the wires of Examples No. 20 to 26, 34 to 36 containing 1 mass ppm or more of the second additive element in total brought a better bonding reliability of the first joint under a high temperature and high humidity environment. It was confirmed that the wires of Examples No. 3, 7, 11, and 27 to 36 containing 0.011 mass % or more of the third additive element in total brought a better bonding reliability of the first joint under a high temperature environment.
[0259] On the other hand, it was confirmed that the wires of Comparative Examples Nos. 1 to 12 had a coating layer that did not satisfy at least one of the conditions (1) and (2) specified in the present invention, and that the shape stability of the second joining portion was poor.
[0260] Industrial Availability
[0261] 1Joint line (wire)
[0262] 2 Measurement surface
[0263] 10 Second joint
[0264] 10w Deformation width of the second joint (deformation width in the direction perpendicular to the axis of the wire)
[0265] Axis of the X-line (center of the line width)
[0266] Width of W wire (wire diameter)
[0267] w a Width of measuring surface
[0268] l a Measuring surface length
Claims
1. A bonding wire for a semiconductor device, comprising a core material composed of Cu or a Cu alloy and a coating layer containing a conductive metal other than Cu formed on the surface of the core material, The average size of the crystal grains in the circumferential direction of the wire obtained by analyzing the surface of the wire by electron backscatter diffraction is 35 nm to 140 nm. In the concentration distribution in the depth direction of the line measured by Auger electron spectroscopy, the region from the surface to a depth of 10 nm, that is, region d 0-10 Contains three or more elements selected from the group consisting of Pd, Pt, Au, Ni, and Ag, and satisfies the following concentration conditions (i) and (ii): (i) Regarding area d 0-10 At least three of the three or more elements contained in the region d 0-10 The average concentration of each element in the (ii) Regarding area d 0-10 All of the three or more elements contained in the region d 0-10 The average concentration of each element in the carbon nanotubes is less than 80 atomic %.
2. The bonding wire according to claim 1, The thickness of the coating layer is not less than 40 nm and not more than 200 nm.
3. The bonding wire according to claim 1 or 2, In the results of measuring the crystal orientation of the surface of the wire by electron backscatter diffraction, the crystal orientation in the wire length direction with an angle difference of 15 degrees or less relative to the wire length direction is <111> The ratio of the crystal orientation is 30% or more and 95% or less.
4. The bonding wire according to any one of claims 1 to 3, The concentration distribution in the depth direction of the wire was obtained by digging down from the surface of the wire by Ar sputtering and measuring by Auger electron spectroscopy under the following conditions: Conditions: Positioning is performed so that the center of the wire width is the center of the measurement surface width, the measurement surface width is 5% to 15% of the wire diameter, and the measurement surface length is 5 times the measurement surface width.
5. The bonding wire according to any one of claims 1 to 4, The wire contains a first additional element which is one or more elements selected from the group consisting of B, P, In, and Mg, and the total concentration of the first additional element relative to the entire wire is 1 mass ppm or more and 100 mass ppm or less.
6. The bonding wire according to any one of claims 1 to 5, The wire contains a second additional element which is one or more elements selected from the group consisting of Se, Te, As, and Sb, and the total concentration of the second additional element with respect to the entire wire is 1 mass ppm or more and 100 mass ppm or less.
7. The bonding wire according to any one of claims 1 to 6, A third additional element which is one or more elements selected from the group consisting of Ga, Ge, and Ag is contained, and the total concentration of the third additional element with respect to the entire wire is 0.011 mass % or more and 1.5 mass % or less.
8. A semiconductor device, Comprising the bonding wire according to any one of claims 1 to 7.
Citation Information
Patent Citations
Copper alloy wire for connecting semiconductor element
JP1986048543A
Bonding wire and integrated circuit device using the same
JP2005167020A
Corrosion and Moisture Resistant Copper Based Bonding Wire Containing Nickel
JP2018503743A
Semiconductor device and manufacturing method thereof
JP2020150116A
Bonding wire for semiconductor device
WO2017013796A1